Editorial: Small cetacean conservation: Current challenges and opportunities - Kiszka, Jeremy J. (2022)
Dolphins (oceanic and river dolphins; Delphinidae, Iniidae, Lipotidae, Pontoporiidae, Platanistidae) and porpoises (Phocoenidae) are the smallest members of the odontocete suborder. These species have colonized most aquatic ecosystems globally, from rivers to deep oceanic habitats, and from tropical to polar waters. Due to their habitat preferences, high metabolic rates, foraging behaviors, and diets, small cetaceans exhibit a wide range of ecological roles and functions across ecosystems where they occur and have the potential to affect communities via multiple pathways (top-down, bottom-up effects, and a range of behavior-mediated processes, Kiszka et al.). Dolphins and porpoises have also generated significant interest from the scientific community and more broadly by human societies since antiquity, with research on these animals increasing exponentially over the past 40-50 years. Despite protection by a range of international conventions (e.g., Convention on Migratory Species, Convention on the Trade of Endangered Species) and national legislation in most countries, some species are at increasing risk of decline and extirpation in aquatic habitats worldwide, with losses driven by a range of direct and indirect impacts from human activities. Today, more than 20% of species of oceanic dolphins, half of all species of porpoise, and all river dolphins are threatened with extinction